Unlicensed and off label prescribing of drugs in general practice. Issue 6 (1st December 2000) - McIntyre, J; Conroy, S; Avery, A; Corns, H; Choonara, I
Abstract : AIM: To determine the incidence and nature of unlicensed and off label prescribing of drugs for children in general practice. METHODS: A retrospective analysis of all prescriptions for one year involving children (aged 12 years or under) from a single suburban general practice in the English Midlands. Prescribed drugs were categorised as licensed, unlicensed (without a product licence), or used in an off label way (outside the terms of their product licence). RESULTS: During 1997 there were 3347 prescription items involving 1175 children and 160 different drugs. A total of 2828 (84.5%) prescriptions were for licensed medicines used in a licensed way; 10 (0.3%) were for unlicensed medicines; and 351 (10.5%) were licensed medicines used in an off label way. For 158 (4.7%) the information was insufficient to determine licence status. CONCLUSION: This is the first study to show that a significant number of drugs prescribed for children by general practitioners are off label and highlights the anomalies and inadequacies of drug information for prescribers.